Evaluation of ferric chloride and electroflocculation of Chlorella pyrenoidosa and reuse of the culture medium for subsequent cultures. Issue 1 (February 2020) - Mubarak, M.; Shaija, A.; Suchithra, T.V.
Abstract: In this study, the different harvesting methods of Chlorella pyrenoidosa such as centrifugation, filtration, and flocculation with parameters such as pH, presence of alum and FeCl3 also studied were compared based on harvesting efficiency. Among these methods, flocculation using FeCl3 and electroflocculation using iron electrodes showed highest efficiencies of 98.5 and 95 %, respectively. Then, the optimization of parameters such as concentration of flocculant, biomass concentration and time for flocculation using FeCl3 was performed using Taguchi method of experimental design. The same procedure was followed for the optimization of parameters such as biomass concentration, time, current and voltage used in electroflocculation. At optimized conditions of the flocculation using FeCl3 and electroflocculation showed flocculation efficiencies of 98.84 % and 96.75 %, respectively. The flocculated medium obtained under optimized conditions of the two methods are used for the cultivation of C. pyrenoidosa with supplemented fresh Bold basal media of 20 %, 40 %, 60 % and 80 %. The biomass concentration and lipid content of C. pyrenoidosa was measured and compared with fresh Bold basal media and flocculated media cultivation without medium supplement. The results showed maximum biomass concentrations in g/l of 0.86, 0.82, 0.72, 0.71 and 0.68, respectively for 80 %, 60 %, 40 % and 20 % fresh BBM supplemented and FeCl3 flocculated media as compared to 0.98  g /l for fresh BBM. The results showed maximum biomass concentrations in g/l of 0.88, 0.86, 0.83, 0.78 and 0.76, respectively for 80 %, 60 %, 40 % and 20 % fresh BBM supplemented and electro flocculated media as compared to 0.98 g/l for fresh BBM.